Exercise Training Improves Heart Rate Recovery after Exercise in Hypertension - Graziela Amaro-Vicente; Mateus C. Laterza; Daniel G. Martinez; Maria Janieire N. N. Alves; Ivani C. Trombetta; Ana Maria F. W. Braga; Edgar Toschi-Dias; Maria Urbana P. B. Rondon
Abstract Aim: This study tested the hypothesis that: 1- the exercise training would improve the heart rate recovery (HRR) decline after maximal exercise test in hypertensive patients and; 2- the exercise training would normalize HRR decline when compared to normotensive individuals. Methods: Sixteen hypertensive patients were consecutively allocated into two groups: Exercise-trained (n = 9, 47±2 years) and untrained (n = 7, 42±3 years). An exercise-trained normotensive group (n = 11, 41±2 years) was also studied. Heart rate was evaluated by electrocardiogram. The autonomic function was evaluated based on heart rate changes on the first and the second min of recovery after the maximal exercise test. Exercise training consisted of three 60-minute exercise sessions/week for 4 months. Results: In hypertensive patients, exercise training significantly increased the HRR decline in the first (-19±2 vs. -34±3 bpm, P = 0.001) and second (-33±3 vs. -49±2 bpm, P = 0.006) minutes after the maximal exercise test. In addition, after exercise training, the initial differences in the HRR decline after exercise between hypertensive patients and normotensive individuals were no longer observed (first minute: -34±3 vs. -29±3 bpm, P = 0.52, and second minute: -49±2 vs. -47±4 bpm, P = 0.99). Conclusion: Hypertension causes a delay in HRR after the maximal exercise test yet the exercise training normalizes HRR during the post-exercise period in hypertensive patients.